THE ENTREPRENEURSHIP LEARNING MODEL IMPROVES THE COMPETENCE OF ENTREPRENEURS - Suranto Suranto; Agus Marimin; Munajat Tri Nugroho; M Fahmi Johan Syah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
To generate college graduates who are competitive, independent, ready to work and have entrepreneurial competencies will require hard work, both the learning process, learning strategies, regulations, curriculum, supporting infrastructure, methods and appropriate regulations to make it occur. This research aims to enhance entrepreneurial mental competence for students. The benefits of the research are that a goodness of fit entrepreneurship learning model is generated for enhancing entrepreneurial competence and a role model for increasing student entrepreneurial competence. The object of the research is students who take entrepreneurship lectures in the Industrial Engineering study program at Universitas Muhammadiyah Surakarta. Data collection methods are conducted with questionnaires, observation, documentation and direct action of students doing entrepreneurial learning activities. Stages of implementation through workshops, business internships, product manufacturing and design, and product marketing. Data analysis with structural equational modeling (SEM) concept approach build variable linkages and model formulation. Based on the results of the analysis, the model developed is declared goodness and fit so that it is feasible to use to develop an entrepreneurial learning model in order to enhance student entrepreneurial competence.